Influence of Cr2O3 doping on the electrical characteristics of novel ZnO-Cr2O3-based varistor ceramics. (March 2023) - Tian, Tian; Zheng, Liaoying; Bernik, Slavko; Man, Zhenyong; Shi, Xue; Ruan, Xuezheng; Li, Guorong
Highlights: About 0.1 mol.% of Cr2 O3 is optimal for the formation of the increased electrostatic double Schottky barriers height and thus an enhanced coefficient of nonlinearity α = 74 and a lower leakage current ( I L < 0.2 μA/cm 2 ). Small amounts of added Cr2 O3 primarily result in the formation of acceptor defects at the GBs for enhanced electrostatic Schottky barriers, which leads to an enhanced current-voltage ( I - V ) nonlinearity and a decrease of the leakage current. For larger additions of Cr2 O3 (above 0.20 mol.%) the Ca3 (CrO4 )2 phase starts to form, which led to a decreased barrier height and thus a decreased I - V nonlinearity with an α value of 25 and an increased leakage current ( I L > 5 mA/cm 2 ). Abstract: Novel ZnO-Cr2 O3 -based varistors can overcome the problems related to the volatile, high-cost and toxic components of conventional ZnO-Bi2 O3 -, ZnO-Pr6 O11 -, and ZnO-V2 O5 -based varistors. The influence of the varistor former with different doping levels, i.e., the Cr2 O3, on the microstructure and electrical properties was examined and the optimal amount of Cr2 O3 doping to enhance the electrical performance of ZnO-Cr2 O3 -based varistor ceramics was determined. The results showed that about 0.1 mol.% of Cr2 O3 is optimal for the formation of the electrostatic double Schottky barriers with increased height at the grain boundaries (GBs) and thus an enhanced I - V nonlinearity (i.e., a coefficient of nonlinearity α = 73) and a lower leakage current ( I L < 0.2 μA/cm 2 ) in ZnO-Cr2 O3 -based varistor ceramics with an E b of 383 V/mm. For larger additions of Cr2 O3, a Ca3 (CrO4 )2 phase forms, which decreases the barrier height and leads to a lowering of α and an increase in I L . Graphical abstract: Image, graphical abstract